Mechanical properties of crumb rubber-rice husk ash concrete as a rigid pavement material. (October 2019) - Abdurrahman, H; Wibisono, G; Qoryati, M; Sitompul, I R; Olivia, M
Abstract: Waste tyres accumulate very quickly in a landfill as a result of the fast development of the transport industry, and mainly automobiles. The polymeric waste has limited usage and is rarely employed in a highly economic and viable product. A rigid pavement material needs to have high mechanical properties and durability when exposed to aggressive environments. In this research, a combination of waste tyre with rice husk ash and Portland Cement Composite (PCC) as a primary binder was designed to produce concrete that meets the requirements of flexural strength value of the rigid pavement based on the Indonesian Standard from Bina Marga 2018. Eight mixes with a variety of water/cement ratio (0.30-0.40), crumb rubber (2.5-7.5%), and rice husk ash (7.5-10%) were designed in this research. The control mix was PCC concrete. The crumb rubber substituted the fine aggregate content, while the rice husk ash replaced the cement content in concrete. The specimens were cast and subsequently cured in water pond up to 28 days. The mechanical properties of concrete, namely compressive strength and flexural strength were determined for all variations. Based on the results, Mix 1 with w/c ratio of 0.30, crumb rubber of 5%, and rice husk ash of 10%, performed both the highest compressive strength and flexural strength values of 36.38 MPa and 4.53 MPa, respectively, after 28 days. Both values fulfilled the requirements of the Indonesian Standard Bina Marga 2018. It can be concluded that an appropriate combination of crumb rubber and rice husk ash improves the mechanical properties of the concrete and has potential as a rigid pavement material.